A Genetic Score Associates With Pioglitazone Response in Patients With Non-alcoholic Steatohepatitis - Kawaguchi-Suzuki, Marina; Cusi, Kenneth; Bril, Fernando; Gong, Yan; Langaee, Taimour; Frye, Reginald F. (Frontiers in Pharmacology, 2018)
Pioglitazone is used effectively to treat nonalcoholic steatohepatitis (NASH), but there is marked variability in response. This study examined whether genetic variation contributes to pioglitazone response variability in patients with NASH. This genetic substudy includes 55 participants of a randomized controlled trial designed to determine the efficacy of long-term pioglitazone treatment in patients with NASH. The primary outcome of the clinical trial was defined as ≥ 2-point reduction in the nonalcoholic fatty liver disease activity score (NAS). In this substudy, single nucleotide polymorphisms (SNPs) in putative candidate genes were tested for association with primary and secondary outcomes. A genetic response score was constructed based on the sum of response alleles for selected genes. The genetic response score was significantly associated with achievement of the primary outcome (odds ratio 1.74; 95% CI 1.27-2.54; p=0.0015). ADORA1 rs903361 associated with resolution of NASH (p=0.0005) and change in the ballooning score among Caucasian and Hispanics patients (p=0.0005). LPL rs10099160 was significantly associated with change in ALT (p=0.0005). The CYP2C8*3 allele, which confers faster pioglitazone clearance in allele carriers, was associated with change in fibrosis score (p=0.026). This study identified key genetic factors that explain some of the inter-individual variability in response to pioglitazone among patients with NASH.